The role and practice of the genetic nurse: report of the AGNC Working Party. Issue 2 (February 1997) - Skirton, H; Barnes, C; Curtis, G; Walford-Moore, J
Abstract : The role of the genetic nurse has evolved historically with the emergence of clinical genetics in the field of health care. During 1994, a Practice Working Party was convened by the Genetic Nurses and Social Workers Association in response to discussion about the role of the nurse within and between regional genetics centres. The Working Party conducted a study of the current nursing practice and attitudes of nurses and clinicians to the nursing role, as a basis for future discussion and planning for educational needs. This paper describes the role of the genetic nurse within the United Kingdom and offers suggestions for assessment of competency. Strong themes emerging from respondents' comments include the need and desire for multi-professional team work, and it is apparent that most respondents felt the families' needs would best be served by a skilful combination of medical and nursing input, rather than adherence to traditional roles.